The impact of climate change on fish infectious diseases (a review) - Yu. Rud; O. Zaloilo; L. Buchatsky; I. Hrytsyniak (Ribogospodarsʹka Nauka Ukraïni, 2020)
Purpose. As the climate change impacts freshwater and marine ecosystems, and rising ocean temperatures and acidification continue to this moment, our aim was to analyze the literature and summarize information on the development of fish infectious diseases in the light of global warming.